Peningkatan Hasil Belajar Pak Materi Terlibat Dalam Hidup Menggereja Dengan Metode Problem Based Learning Kelas V SDN Banyuagung 1 Kota Surakarta - Agustina Yulianti; Hartutik Hartutik; Paulus Asriadi (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Teachers usually apply lecture and teacher-centred methods during the learning process, making students less able to understand Catholic religious material and tend to get bored. The aim of the research is to determine the increase in mutual cooperation aspects, determine the success of achieving targets, determine the increase in learning outcomes using the Involved Material Problem Based Learning Method. In the Life of Churching among fifth grade students at SD Negeri Banyuagung 1 Surakarta. The research method used is Classroom Action Research with four stages, namely planning, implementation, evaluation and reflection with two cycles in the offline learning process. Research Subjects were students of SD Negeri Banyuagung 1 Surakarta class V Semester 1 of the 2023/2024 academic year with a total of 6 people in the period 27 October 2023 to 3 November 2023. The material was Involved in Church Life. Cycles 1 and 2 each have 3 lesson hours. The results of the research show that mutual cooperation activities in each indicator have increased, as seen from the average percentage of 76.88% in cycle 1, increasing to 88.21% in cycle 2. This means that mutual cooperation activities have increased by 11.33%. The learning outcomes show progress after implementing the problem based learning model. It can be seen that in the advanced category the percentage obtained was 17% in cycle 1, increasing to 83% in cycle 2, meaning that in the advanced category there was an increase of 66%. In the proficient category there was a decrease of 16%, from 33% in cycle 1 to 17% in cycle 2. In the decent category there was also a decrease of 50%, from 50% in cycle 1 to 0% in cycle 2. And in the new category it developed there was no change, namely 0% in both cycle 1 and cycle 2. In this case, teachers should use the Problem Based Learning Method as an alternative learning method because it has been proven that this Problem Based Learning Method can improve aspects of student learning outcomes.